POLR3B-associated leukodystrophy: clinical, neuroimaging and molecular-genetic analyses in four patients: clinical heterogeneity and novel mutations in POLR3B gene - Kulhánek, Jan; Brožová, Klára; Hansíková, Hana; Vondráčková, Alžběta; Stránecký, Viktor; Šenkyřík, Jan; Kmoch, Stanislav; Zeman, Jiří; Honzík, Tomáš; Tesařová, Markéta (Neurologia i Neurochirurgia Polska, 2019)
INTRODUCTION AND AIM OF THE STUDY: White matter disorders represent a spectrum of neurological diseases frequently associated with an unfavourable prognosis and a delay in diagnostics. We report the broad phenotypic spectrum of a rare hypomyelinating leukodystrophy and three novel mutations. Further, we aim to explore the role of the combined clinical and neuroimaging diagnostic approach in the era of whole exome sequencing. MATERIALS AND METHODS: We present a clinical, neuroimaging and molecular-genetic characterisation of four patients from three families suffering from a rare genetic leukoencephalopathy. Two severely affected siblings (P1, P2) manifested a profound developmental delay, cerebellar symptomatology, microcephaly, failure to thrive, short stature and delayed teeth eruption with oligodontia. The other two patients (P3, P4), on the contrary, suffer from substantially less serious impairment with mild to moderate developmental delay and cerebellar symptomatology, delayed teeth eruption, or well-manageable epilepsy. In all four patients, magnetic resonance revealed cerebellar atrophy and supratentorial hypomyelination with T2-weight hypointensities in the areas of the ventrolateral thalamic nuclei, corticospinal tract and the dentate nuclei. RESULTS: Using whole-exome sequencing in P1, P2 and P3, and targeted sequencing in P4, pathogenic variants were disclosed in POLR3B, a gene encoding one of 17 subunits of DNA-dependent RNA polymerase III - all patients were compound heterozygotes for point mutations. Three novel mutations c.727A>G (p.Met243Val) and c.2669G>A (p.Arg890His) (P1, P2), and c.1495G>A (p.Met499Val) (P3) were found. Magnetic resonance revealed the characteristic radiological pattern of POLR3-leukodystrophies in our patients. CONCLUSION AND CLINICAL IMPLICATIONS: The diagnosis of POLR3-associated leukodystrophies can be significantly accelerated using the combined clinical and neuroradiological recognition pattern. Therefore, it is of crucial importance to raise the awareness of this rare disorder among clinicians. Molecular-genetic analyses are indispensable for a swift diagnosis confirmation in cases of clear clinical suspicion, and for diagnostic search in patients with less pronounced symptomatology. They represent an invaluable tool for unravelling the complex genetic background of heritable white matter disorders.
Keywords: mutace; RNA-polymerasa III; dědičné demyelinizační nemoci CNS; nemoci mozečku; Hereditary Central Nervous System Demyelinating Diseases; neurozobrazování; Cerebellar Diseases; RNA Polymerase III; lidé; Mutation; Neuroimaging; Humans